PENGARUH JUMLAH USAHA DAN INVESTASI TERHADAP JUMLAH TENAGA KERJA INDUSTRI MENENGAH KOTA SURABAYA - Fahad Ainun Saleh; Aris Soelistyo; Hendra Kusuma (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of the number mid-industrial and investment to the labor of mid-industrial in Surabaya during the period 2017-2019. This study used panel data regression with common effect method (CEM). The data used in this research is secondary data. The variables dependent used in this study is the number of labor in Surabaya, while the independent variable are number mid-industrial and investment mid-industrial of Surabaya. Panel data regression calculation results in this study indicate that a variable number mid-industrial and investment simultaneously have a positive influence and significant impact on labor mid-industrial in Surabaya. Partially, variable number mid-industrial and investment have a positive influence and significant impact on labor mid-industrial in Surabaya.